2020
DOI: 10.3390/molecules25092072
|View full text |Cite
|
Sign up to set email alerts
|

Stability Evaluation of DMT and Harmala Alkaloids in Ayahuasca Tea Samples

Abstract: Ayahuasca tea is a hallucinogenic beverage used for religious purposes in Brazil and many other countries that has therapeutic potential in the treatment of some mental health disorders. In the context of psychedelic research, quantification of the tea’s main alkaloids prior to its administration in animal or human studies is essential. For this reason, this study aims to provide information regarding the stability of the main ayahuasca alkaloids (dimethyltryptamine, DMT; harmine, HRM; tetrahydroharmine, THH; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
(51 reference statements)
2
18
0
1
Order By: Relevance
“…These differences in the ayahuasca preparation may indeed impact the β-carboline ratios, although a clear pattern could not be seen in the seven Daime honey samples analyzed in this study ( Table S2 ). A recent study showed that THH is stable in ayahuasca samples for about 9 days at 37 °C, simulating an extreme transport and storage situation, while harmine and harmaline concentrations vary under the same conditions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in the ayahuasca preparation may indeed impact the β-carboline ratios, although a clear pattern could not be seen in the seven Daime honey samples analyzed in this study ( Table S2 ). A recent study showed that THH is stable in ayahuasca samples for about 9 days at 37 °C, simulating an extreme transport and storage situation, while harmine and harmaline concentrations vary under the same conditions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing the plants in the country where the session is to take place and the plant materials being fresh is likely to be important in ensuring quality (de Oliveira Silveira et al, 2020). However, freezedried ayahuasca can be safely administered with the desired effects (dos .…”
Section: Ayahuascamentioning
confidence: 99%
“…The UPLC-MS/MS analysis, which has previously proven to be suitable for the analysis of ayahuasca tea samples (de Oliveira Silveira et al, 2020 ), has shown to be similarly adequate for the identification and quantification of all analytes in urine specimens using an 8-min chromatographic run as shown in Figure 1 . Although chromatographic separation is not mandatory when using MRM, special attention was given to HRL and HRM separation since initial experimentation has demonstrated possible ion suppression for HRL when overlapped with HRM.…”
Section: Resultsmentioning
confidence: 98%